Retrospective analysis of pharmacist interventions in an ambulatory palliative care practice. (December 2016) - Ma, Joseph D; Tran, Victor; Chan, Carissa; Mitchell, William M; Atayee, Rabia S
Background: We have previously reported the development of an outpatient palliative care practice under pharmacist–physician collaboration. The Doris A. Howell Service at the University of California, San Diego Moores Cancer Center includes two pharmacists who participate in a transdisciplinary clinic and provide follow-up care to patients. Objective: This study evaluated pharmacist interventions and patient outcomes of a pharmacist-led outpatient palliative care practice. Methods: This was a retrospective data analysis conducted at a single, academic, comprehensive cancer center. New (first visit) patient consultations were referred by an oncologist or hematologist to an outpatient palliative care practice. A pharmacist evaluated the patient at the first visit and at follow-up (second, third, and fourth visits). Medication problems identified, medication changes made, and changes in pain scores were assessed. Results: Eighty-four new and 135 follow-up patient visits with the pharmacist occurred from March 2011 to March 2012. All new patients ( n = 80) were mostly women ( n = 44), had localized disease ( n = 42), a gastrointestinal cancer type ( n = 21), and were on a long-acting ( n = 61) and short-acting ( n = 70) opioid. A lack of medication efficacy was the most common problem for symptoms of pain, constipation, and nausea/vomiting that was identified by the pharmacist at all visits. A change in pain medication dose and initiation of a new medication for constipation and nausea/vomiting were the most common interventions by the pharmacist. A statistically significant change in pain score was observed for the third visit, but not for the second and fourth visits. Conclusions: A pharmacist-led outpatient palliative care practice identified medication problems for management of pain, constipation, and nausea/vomiting. Medication changes involved a change in dose and/or initiating a new medication. Trends were observed in improvement and stabilization of pain over subsequent clinic visits.